HUBUNGAN JOB INVOLVEMENT, ORGANIZATIONAL COMMITMENT, PROFESSIONAL COMMITMENT DAN TEAM COMMITMENT: PERBANDINGAN GENERASI X DAN GENERASI Y DI FIFGROUP - Glen Samuel; Theresia Dwinita Laksmidewi (Prosiding Working Papers Series In Management, 2018)
The purpose of this study is to determine whether there is a difference between Generation X and Generation Y in terms of Job Involvement, Organizational Commitment, Professional Commitment and Team Commitment. In addition, this study also looks at the relationship between Job Engagement, Organizational Commitment, Professional Commitment and Team Commitment.Sampling method in this research is convenience sampling. The research was conducted at the FIFGROUP. By using a sample of 91 respondents consisting of 42 respondents X generation and 49 respondents Y generation. Data analysis method using SPSS 22 with One Way ANOVA analysis. Based on the findings generated from this study there is a difference between Generation X and Generation Y, where Y generation has a higher Commitment, Commitment, Commitment Commitment and Team Commitment level than X generation, and other findings found no relationship between work involvement variables to affective commitment variables, continuous commitment, normative commitment, professional commitment and team commitment Keywords: Generation X, Generation Y, Job Involvement, Organizational Commitment, Professional Commitment, Team Commitment.